Evaluation of physical properties of autoclaved aerated concrete (AAC) based glass-gypsum waste into concrete / Izzati Abdul Manaf ... [et al.] - Abdul Manaf, Izzati; Marsi, Noraini; Yusrianto, Efil; Salamat, Muhammad Hafifi Daniel; Kassim, Noraniah; Awang, Mariah; Shariff, Hafizuddin Hakim; Mohd Jamir, Mohd Ridzuan; Ali, Roslinda (Universiti Teknologi MARA, 2022)
The world produces billions of tonnes of municipal solid waste (MSW) yearly, with part of it not being disposed of properly. To approach sustainable development and reduce waste in landfill, using waste in material production is proposed. According to the World Green Building Council, construction projects have expanded and demand for green buildings is likely to increase in the next three years. Autoclaved aerated concrete (AAC) is considered as an environmentally friendly product compared to standard concrete and bricks. This paper aims to investigate the influence of glass waste (GW) and gypsum wastes as additional materials on the physical properties and compressive strength of AAC is to determine the optimum proportion of GW addition to produce AAC based glass-gypsum waste (AAC-GGW) and to compare the properties of AAC-GGW with reference sample. The materials used were ordinary Portland cement (OPC), quartz sand, lime, aluminium paste, GW and gypsum waste. The ratios of all materials were kept constant except GW with increment of 0%, 5%, 10%, 15%, 20%, 25%, and 30%. The density, water absorption, porosity, and average compressive strength of the samples were measured and compared. It was found that increasing GW increased the samples' density and decreased the samples' water absorption and porosity. It was also found that addition of GW from 5 to 25% achieved better average compressive strength than reference sample with no addition of GW. Maximum compressive strength was achieved at 20% GW addition.